2004
DOI: 10.1016/j.febslet.2004.04.069
|View full text |Cite
|
Sign up to set email alerts
|

Rac1 and PAK1 are upstream of IKK‐ε and TBK‐1 in the viral activation of interferon regulatory factor‐3

Abstract: The anti-viral type I interferon (IFN) response is initiated by the immediate induction of IFNb, which is mainly controlled by the IFN-regulatory factor-3 (IRF-3). The signaling pathways mediating viral IRF-3 activation are only poorly defined. We show that the Rho GTPase Rac1 is activated upon virus infection and controls IRF-3 phosphorylation and activity. Inhibition of Rac1 leads to reduced IFNb promoter activity and to enhanced virus production. As a downstream mediator of Rac signaling towards IRF-3, we h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
102
2

Year Published

2005
2005
2016
2016

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 117 publications
(106 citation statements)
references
References 36 publications
2
102
2
Order By: Relevance
“…These studies have led to the characterization of new inducers of IRF-3 activity as well as the intracellular signaling pathways leading to IRF-3 activation (38,42,43,55,56). Notably, two IKK homologs, IKKi and TBK1, were shown to be involved in IRF-3 phosphorylation and activation (12)(13)(14)(15)(16)57). Another important issue, which remains poorly understood, is the molecular mechanisms that trigger the degradation of IRF-3 following virus infection.…”
Section: Discussionmentioning
confidence: 99%
“…These studies have led to the characterization of new inducers of IRF-3 activity as well as the intracellular signaling pathways leading to IRF-3 activation (38,42,43,55,56). Notably, two IKK homologs, IKKi and TBK1, were shown to be involved in IRF-3 phosphorylation and activation (12)(13)(14)(15)(16)57). Another important issue, which remains poorly understood, is the molecular mechanisms that trigger the degradation of IRF-3 following virus infection.…”
Section: Discussionmentioning
confidence: 99%
“…We therefore went on to address whether this unique phosphorylation plays a physiological role in the regulation of IRF3 function. Although JNK could also stimulate the transcriptional activity of another transcription factor, alkaline phosphatase (AP-1), the PRD III-I-Luciferase reporter was responsive only to IRF3 activation in the context of LPS stimulation [39]. As shown in Figure 4A, luciferase analysis revealed that inhibition of endogenous JNK activation by SP600125 significantly impaired gene expression induced by LPS, which reduced the expression level below the basal level.…”
Section: Jnk Regulates Irf3-mediated Gene Expression Induced By Lps Amentioning
confidence: 98%
“…pcDNA3-TBK1 and pcDNA3-IKKe expression plasmids were kind gifts from Dr K. Fitzgerald (Fitzgerald et al, 2003). The reporter plasmid (PRDIII-I) 4 -Luc was kindly provided by Dr S. Ludwig (Ehrhardt et al, 2004).…”
Section: Methodsmentioning
confidence: 99%
“…pcDNA3-TBK1 and pcDNA3-IKKe expression plasmids were kind gifts from Dr K. Fitzgerald (Fitzgerald et al, 2003). The reporter plasmid (PRDIII-I) 4 -Luc was kindly provided by Dr S. Ludwig (Ehrhardt et al, 2004).Transfection and reporter assay. 293T cells were seeded in 35 mm dishes and co-transfected with empty vector or plasmids encoding the PRRSV proteins, Renilla luciferase plasmid phRL-TK and reporter plasmid p125-Luc, PRD(III-I)4-Luc or pNF-kB-Luc.…”
mentioning
confidence: 99%